2022
DOI: 10.1186/s12889-021-12490-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between childhood sexual abuse and attitudes toward premarital sexual permissiveness among middle school students in Luzhou, China

Abstract: Background In recent years, the number of adolescents engaging in premarital sex has increased, and an increasing number of childhood sexual abuse (CSA) cases have been reported in China. Many studies have indicated that CSA has a well-established association with risky sexual activities. However, only a limited number of studies have explored possible reasons for this association among middle school students, a population that may engage in premarital sex, which is critical for the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
2
8
1
Order By: Relevance
“…According to the theory of planned behaviour (TPB) [24], individual behaviour is in uenced by a combination of three factors: behavioural attitudes, subjective norms, and perceived behavioural control. In addition, earlier ndings from our research group showed that middle school students who had experienced CSA were more likely to have open attitudes about premarital sex [25]. CSA may also cause individuals who experience it to question social norms about sex and sexuality, which may in uence their sexual behaviour.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…According to the theory of planned behaviour (TPB) [24], individual behaviour is in uenced by a combination of three factors: behavioural attitudes, subjective norms, and perceived behavioural control. In addition, earlier ndings from our research group showed that middle school students who had experienced CSA were more likely to have open attitudes about premarital sex [25]. CSA may also cause individuals who experience it to question social norms about sex and sexuality, which may in uence their sexual behaviour.…”
Section: Introductionmentioning
confidence: 72%
“…If a respondent answered "yes" to any of the above questions, he or she was de ned as having experienced CSA. Referring to the previous research [25], we classi ed the above 11 survey items into three categories: a ~ d were considered sexual harassment, e ~ i were considered sexual molestation, and j ~ k were considered sexual assault. We then identi ed four severity levels of CSA according to the following classi cation: "no" referred to none of the above categories being experienced.…”
Section: Childhood Sexual Abusementioning
confidence: 99%
See 1 more Smart Citation
“…In China, there has been a shift in attitudes from being conservative to being open to premarital sex. Many influences from western culture, openness of the digital economy, policies on the age of marriage and early puberty support the agreeable attitude of premarital sex so that it is directly proportional to the prevalence of premarital sex behavior (Rong et al, 2022).…”
Section: Premarital Sex Attitudes and Risky Behaviormentioning
confidence: 99%
“…In most countries, the shift towards later marriage in recent decades has led to an increase in premarital sex, making sexual health in relation to premarital sex an important public health issue [ 1 ]. Contemporary Chinese college students have open attitudes towards premarital sexual behaviour, and premarital sex is common among college students [ 2 ]. The premarital sex rate reported in China from 2011 to 2019 ranged from 13.36 to 30.4%, accompanied by an increasing trend year by year [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%